2020
DOI: 10.1186/s12877-020-1488-1
|View full text |Cite
|
Sign up to set email alerts
|

Informal caregivers’ views on the quality of healthcare services provided to older patients aged 80 or more in the hospital and 30 days after discharge

Abstract: Background: In the European Union (EU), informal caregivers provide 60% of all care. Informal caregiving ranges from assistance with daily activities and provision of direct care to helping care recipients to navigate within complex healthcare and social services systems. While recent caregiver surveys document the impact of informal caregivers, systematic reviews show that they have unmet needs. Because of the political desire to reduce the length of hospital stays, older patients are discharged from the hosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 50 publications
(48 reference statements)
3
30
0
7
Order By: Relevance
“…61 The relationship with healthcare professionals is another important aspect of caring responsibility. In line with the literature [62][63][64][65] and policies 53,66 emphasizing the importance of person-centered care, the participants in our study appreciated when healthcare professionals acknowledged the older person as an individual in a vulnerable life context. Unfortunately, the opposite was also evident, as reflected in experiences with disinterested healthcare professionals displaying no mindful attention to the situation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…61 The relationship with healthcare professionals is another important aspect of caring responsibility. In line with the literature [62][63][64][65] and policies 53,66 emphasizing the importance of person-centered care, the participants in our study appreciated when healthcare professionals acknowledged the older person as an individual in a vulnerable life context. Unfortunately, the opposite was also evident, as reflected in experiences with disinterested healthcare professionals displaying no mindful attention to the situation.…”
Section: Discussionsupporting
confidence: 79%
“…In a welfare state, like Denmark, expectations of professional care and system responsibility may be high; however, in line with a study by Lilleheie et al, 64 the participants also expressed an understanding that healthcare systems were subject to pressure and needed more resources and competencies. The older persons and their adult children seemed to accept living with the consequences of more extensive and complex care and treatment being transferred from hospitals to primary healthcare.…”
Section: Discussionsupporting
confidence: 74%
“…Since transitions from one care organization to another are common in the LYOL, this might explain the low degree of satisfaction. Other studies from the perspective of informal caregivers have also observed problems in discharge management and unorganized transitions [ 30 ]. Future surveys using the same instrument may observe improvements in discharge management.…”
Section: Discussionmentioning
confidence: 99%
“…Informal caregivers are family members, friends or neighbours that provide unpaid long-term care for the significant other. The European population consists of 10%-25% of informal caregivers, providing up to 60% of the total care (Lilleheie et al, 2020;Zigante, 2018).…”
Section: Introductionmentioning
confidence: 99%